author | wenzelm |
Mon, 23 Oct 2000 22:17:55 +0200 | |
changeset 10313 | 51e830bb7abe |
parent 10291 | a88d347db404 |
child 11083 | d8fda557e476 |
permissions | -rw-r--r-- |
1475 | 1 |
(* Title: HOL/subset.thy |
923 | 2 |
ID: $Id$ |
1475 | 3 |
Author: Lawrence C Paulson, Cambridge University Computer Laboratory |
923 | 4 |
Copyright 1994 University of Cambridge |
10276 | 5 |
|
6 |
Subset lemmas and HOL type definitions. |
|
923 | 7 |
*) |
8 |
||
7705 | 9 |
theory subset = Set |
10276 | 10 |
files "Tools/induct_attrib.ML" ("Tools/typedef_package.ML"): |
7705 | 11 |
|
9895 | 12 |
(*belongs to theory Ord*) |
13 |
theorems linorder_cases [case_names less equal greater] = |
|
14 |
linorder_less_split |
|
15 |
||
16 |
(*belongs to theory Set*) |
|
17 |
setup Rulify.setup |
|
7717
e7ecfa617443
Added attribute rulify_prems (useful for modifying premises of introduction
berghofe
parents:
7705
diff
changeset
|
18 |
|
10276 | 19 |
|
20 |
section {* HOL type definitions *} |
|
21 |
||
22 |
constdefs |
|
23 |
type_definition :: "('a => 'b) => ('b => 'a) => 'b set => bool" |
|
24 |
"type_definition Rep Abs A == |
|
25 |
(\<forall>x. Rep x \<in> A) \<and> |
|
26 |
(\<forall>x. Abs (Rep x) = x) \<and> |
|
27 |
(\<forall>y \<in> A. Rep (Abs y) = y)" |
|
28 |
-- {* This will be stated as an axiom for each typedef! *} |
|
29 |
||
10290 | 30 |
lemma type_definitionI [intro]: |
10291 | 31 |
"(!!x. Rep x \<in> A) ==> |
32 |
(!!x. Abs (Rep x) = x) ==> |
|
33 |
(!!y. y \<in> A ==> Rep (Abs y) = y) ==> |
|
10290 | 34 |
type_definition Rep Abs A" |
35 |
by (unfold type_definition_def) blast |
|
36 |
||
10276 | 37 |
theorem Rep: "type_definition Rep Abs A ==> Rep x \<in> A" |
38 |
by (unfold type_definition_def) blast |
|
39 |
||
40 |
theorem Rep_inverse: "type_definition Rep Abs A ==> Abs (Rep x) = x" |
|
41 |
by (unfold type_definition_def) blast |
|
42 |
||
43 |
theorem Abs_inverse: "type_definition Rep Abs A ==> y \<in> A ==> Rep (Abs y) = y" |
|
44 |
by (unfold type_definition_def) blast |
|
45 |
||
46 |
theorem Rep_inject: "type_definition Rep Abs A ==> (Rep x = Rep y) = (x = y)" |
|
47 |
proof - |
|
48 |
assume tydef: "type_definition Rep Abs A" |
|
49 |
show ?thesis |
|
50 |
proof |
|
51 |
assume "Rep x = Rep y" |
|
52 |
hence "Abs (Rep x) = Abs (Rep y)" by (simp only:) |
|
53 |
thus "x = y" by (simp only: Rep_inverse [OF tydef]) |
|
54 |
next |
|
55 |
assume "x = y" |
|
56 |
thus "Rep x = Rep y" by simp |
|
57 |
qed |
|
58 |
qed |
|
59 |
||
10284 | 60 |
theorem Abs_inject: |
61 |
"type_definition Rep Abs A ==> x \<in> A ==> y \<in> A ==> (Abs x = Abs y) = (x = y)" |
|
62 |
proof - |
|
63 |
assume tydef: "type_definition Rep Abs A" |
|
64 |
assume x: "x \<in> A" and y: "y \<in> A" |
|
65 |
show ?thesis |
|
66 |
proof |
|
67 |
assume "Abs x = Abs y" |
|
68 |
hence "Rep (Abs x) = Rep (Abs y)" by simp |
|
69 |
moreover note x hence "Rep (Abs x) = x" by (rule Abs_inverse [OF tydef]) |
|
70 |
moreover note y hence "Rep (Abs y) = y" by (rule Abs_inverse [OF tydef]) |
|
71 |
ultimately show "x = y" by (simp only:) |
|
72 |
next |
|
73 |
assume "x = y" |
|
74 |
thus "Abs x = Abs y" by simp |
|
75 |
qed |
|
76 |
qed |
|
77 |
||
10276 | 78 |
theorem Rep_cases: |
79 |
"type_definition Rep Abs A ==> y \<in> A ==> (!!x. y = Rep x ==> P) ==> P" |
|
80 |
proof - |
|
81 |
assume tydef: "type_definition Rep Abs A" |
|
82 |
assume y: "y \<in> A" and r: "(!!x. y = Rep x ==> P)" |
|
83 |
show P |
|
84 |
proof (rule r) |
|
85 |
from y have "Rep (Abs y) = y" by (rule Abs_inverse [OF tydef]) |
|
86 |
thus "y = Rep (Abs y)" .. |
|
87 |
qed |
|
88 |
qed |
|
89 |
||
90 |
theorem Abs_cases: |
|
91 |
"type_definition Rep Abs A ==> (!!y. x = Abs y ==> y \<in> A ==> P) ==> P" |
|
92 |
proof - |
|
93 |
assume tydef: "type_definition Rep Abs A" |
|
94 |
assume r: "!!y. x = Abs y ==> y \<in> A ==> P" |
|
95 |
show P |
|
96 |
proof (rule r) |
|
97 |
have "Abs (Rep x) = x" by (rule Rep_inverse [OF tydef]) |
|
98 |
thus "x = Abs (Rep x)" .. |
|
99 |
show "Rep x \<in> A" by (rule Rep [OF tydef]) |
|
100 |
qed |
|
101 |
qed |
|
102 |
||
103 |
theorem Rep_induct: |
|
104 |
"type_definition Rep Abs A ==> y \<in> A ==> (!!x. P (Rep x)) ==> P y" |
|
105 |
proof - |
|
106 |
assume tydef: "type_definition Rep Abs A" |
|
107 |
assume "!!x. P (Rep x)" hence "P (Rep (Abs y))" . |
|
108 |
moreover assume "y \<in> A" hence "Rep (Abs y) = y" by (rule Abs_inverse [OF tydef]) |
|
109 |
ultimately show "P y" by (simp only:) |
|
110 |
qed |
|
111 |
||
112 |
theorem Abs_induct: |
|
113 |
"type_definition Rep Abs A ==> (!!y. y \<in> A ==> P (Abs y)) ==> P x" |
|
114 |
proof - |
|
115 |
assume tydef: "type_definition Rep Abs A" |
|
116 |
assume r: "!!y. y \<in> A ==> P (Abs y)" |
|
117 |
have "Rep x \<in> A" by (rule Rep [OF tydef]) |
|
118 |
hence "P (Abs (Rep x))" by (rule r) |
|
119 |
moreover have "Abs (Rep x) = x" by (rule Rep_inverse [OF tydef]) |
|
120 |
ultimately show "P x" by (simp only:) |
|
121 |
qed |
|
122 |
||
123 |
setup InductAttrib.setup |
|
124 |
use "Tools/typedef_package.ML" |
|
125 |
||
7705 | 126 |
end |